Tuberculosis and HIV: a global menace exacerbated via sex trafficking. - Dharmadhikari, Ashwin S; Gupta, Jhumka; Decker, Michele R; Raj, Anita; Silverman, Jay G (International journal of infectious diseases : IJID : official publication of the International Society for Infectious Diseases, 2009)
Global tuberculosis (TB) elimination requires recognition and management of TB/HIV co-infected individuals, including those in marginalized and/or understudied populations. We sought to examine the prevalence of TB among repatriated sex trafficked Nepalese girls and women in whom a high HIV prevalence was previously reported.
Keywords: Adolescent; Adult; AIDS-Related Opportunistic Infections; Child; Female; HIV Infections; HIV-1; Humans; Mycobacterium tuberculosis; Nepal; Prevalence; Sex Offenses; Sputum; Tuberculosis; Tuberculosis, Pulmonary; Women's Health; Young Adult